Reducing soak air temperature inside a car compartment using ventilation fans - Mohamed Kamar, Haslinda (Penerbit UTM Press, 2016)
This article presents an investigation on the effects of using ventilation fans on the air temperature inside a car passenger compartment when the car is parked under the sun. It was found from a measurement that the air temperature inside the passenger compartment could raise up to 48°C. Computational fluid dynamics method was used to develop model of the compartment and carry out flow simulations to predict the air temperature distribution at 1 pm for two conditions: without ventilation fans and with ventilation fans. The effects of fan location, number of fans used and fan airflow velocity were examined. Results of flow simulations show that a 17% temperature reduction was achieved when two ventilation fans with airflow velocity of 2.84 m/s were placed at the rear deck. When three fans were used, an additional 3.4% temperature reduction was attained. Placing two ventilation fans at the middle of the roof also reduced the air temperature by 17%. When four fans were used a further 4.8% temperature reduction was achieved. Increasing the airflow velocity at the four fans placed at the roof, from 2.84 m/s to 15.67 m/s, caused only a small reduction in the air temperature inside the passenger compartment.